PHENOTYPIC IDENTIFICATION OF PSEUDOMONAS AERUGINOSA ISOLATED FROM FISH FARMS (CYPRINUS CARPIO) IN MOSUL CITY - Jawad, Asmaa. J. K.; S.Y.A. Al-Dabbagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to isolation and phenotypic characterization of P. aeruginosa. 75 carp fish samples were collected from fish farms at Mosul city during (September2021 to January 2022). Each sample was placed separately in sterile plastic bags and transferred directly to the microbiology laboratory under cooling conditions. The API20-20E assay was used to confirm P. aeruginosa isolates. Also the isolates were confirmed molecularly by polymerase chain reaction assay using the primer 16srDNA. Through bacterial isolation were obtained (60) isolates, which formed (36.6, 30, 8.3, 25 )% of each of the skin, gills, intestines and muscles, respectively. The results showed the sensitivity of P. aeruginosa isolates to impenime (IMP10 µg) and cephalosporin (CIP10 µg) reached (86% and 80 %) respectively, followed by levofloxacin (LEV 5 µg) (74%). But resistant (100%) to both amoxicillin (AM10 µg) and tetracycline (TE10 µg). Isolates varied in their sensitivity and resistance to other antibiotics which included, tobramycin (T0B10 µg), gentamycin (CN10 µg) and amikacin (AK30 µg), the study showed that isolates gave positive results for each hemolytic activity, protease, lecithinase and phospholipase virulence factors tests.